GROWTH OF AFRICAN CATFISH (Clarias gariepinus) JUVENILES FED GRADED LEVELS OF ROASTED RICE CHAFF AS ENERGY SOURCE - Dan-kishiya, Ahmed Salihu; Ekpenwa, C. C. (FUDMA JOURNAL OF SCIENCES, 2020)
The high cost of Maize as energy source in fish feed has necessitated the need to search for low cost and locally available indigenous sources. A six months feeding trial was conducted to examine the effects of replacing maize with roasted rice chaff as a dietary energy source on the growth of juveniles of Clarias gariepinus using Completely Randomized block Design with five different treatments. The fishes were subjected to five different inclusion levels of roasted rice chaff meal (0%, 25%, 50%, 75% and 100%). The trial was conducted in a 50litres plastic bowl with replicates and feeding was done initially at 3% body weight, but the quantity of feeds was adjusted based on the new weight gain. The measurements of the fishes were carried out biweekly according to standard methods and procedures. The Roasted rice chaff meal (RRCM) contains 5.93% crude protein, 14.53% crude fibre, 0.92% moisture content, while Ash content, crude lipid and carbohydrates had 19.98%, 3.28% and 55.36% respectively. Fishes fed 100% RRCM recorded the best growth performance in body weight (435.10 ± 20.60gm), total length (45.30 ± 0.70cm), Specific growth rate (1.44 ± 0.01), Feed Conversion Ratio (2.50 ± 0.04) and Feed Intake (92.00 ± 3.40). While the least growth ware observed in 0% RRCM. However, all the physico-chemical parameters measured are within the recommended range for fish culture. Therefore, the result obtained shows that roasted rice chaff can replace maize as a source of energy in Clarias gariepinus.juveniles diets without any negative effect.